PERLAKUAN AKUNTANSI AKTIVA TETAP BERWUJUD DAN PENYUSUTAN SERTA PENYAJIAN DALAM LAPORAN KEANGAN PADA PT. GEMA GEDUNG ANUGERAH - Sudibyo, Heru Harmadi (Journal of Industrial Engineering & Management Research, 2021)
Fixed assets that have been owned by the company certainly have a time limit for their use so it needs to be a concern by the company relating to the age of the fixed assets. Depreciation is the allocation of the amount of a tangible fixed assets that can be depreciated over the estimated useful life. This research is a descriptive study with a qualitative approach with analytical descriptive analysis techniques with a qualitative approach. Research results of PT. Gema Gedung Anugerah has not made a basis for recording Fixed Tangible Assets, only records the fixed assets based on their benefits regardless of their nominal value. This will result in an immaterial nominal value that can be included in the class of fixed assets, causing it to become a large post for tangible fixed assets.